Initial quantification and characterization of microplastics found in the edible and inedible tissues of Galunggong Decapterus russelli, in Samar sea, Eastern Visayas, Philippines - Oliva, Zaskia A.
This study takes into account the emerging concern of the increasing abundance of MPs in the Philippine marine ecosystem. Particularly, this study aims to investigate the presence of MPs in the inedible and edible tissues of galunggong (Decapterus russelli). Moreover, this study may be the first to report the presence of microplastics in the edible tissues of fish in the Philippines. The present study revealed the presence of MPs in 92% out of the 50 fish samples, mainly consisting of fibers, with an average abundance of 3.96 ± 2.55 MP items/individual (ie, 1.16 ± 0.011 MP items/g). Result from this study is comparable with the findings from other related studies the Philippines (3±0.57 MP items/individual), Indonesia (4.23±0.38 MP items/individual) and in Maldives (2.19 ± 2.0 MP items/individual). The presence of MPs in the edible tissues (ie., skin and muscles) of D. russelli was also confirmed, with an average abundance of 1.78±1.39 MP items/individual (1.e., 0.07 ±0.06 MP items/g). No significant correlation was found between the biological parameters such as its weight, length, and Condition Index (CI), with the amount of MP in the system of the fish. All the fish samples in this study were categorized as "healthy," which suggests that the presence and abundance of MPs may not significantly affect the overall health of the fish in this study. Presence of MPs in the edible and inedible tissues of the fish is still scarcely studied, thus further studies of this nature are much needed to fully understand the implications of MPs at the individual, population, species, and ecosystem levels including its impact to human health.